Clinical Practice Guidelines for Convulsive Condition Management - Victor Rene Navarro Machado; Arelys Falcón Hernández; Maria Octavina Rodríguez Roque (Medisur)
Clinical Practice Guidelines for Convulsive Condition Management. It has been redefined as the occurrence of two or more successive convulsions without conscience recuperation between them; or the occurrence of convulsive uninterrupted activity for more than 5 minutes, including focal crisis. This document includes a review and update of conceptual, etiological and classification aspects for diagnosis and treatment, stressing the various therapy trends. It includes assessment guidelines focused on the most important aspects to be accomplished.